Penerapan Digital Marketing Pada Media Sosial Dalam Upaya Peningkatan Penjualan Produk Learning Course Vocasia Di Jakarta Timur - Muhammad Fauzy Hamdani; Rusdi Hidayat Nugroho (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2023)
In an increasingly digital era, the use of social media has become an important tool in efforts to promote products and reach a wider target market. The development of this digital era can have a positive impact, one of which is in supporting business activities. Digital marketing is currently the choice of many business people in marketing the products to be sold. The purpose of this activity is to explore the application of digital marketing strategies on social media as an effort to increase sales of learning course products at Vocasia. This activity uses a descriptive qualitative approach by collecting data through interviews and observation of the object of research. The results of the study show that the effective use of digital marketing can increase sales of Vocasia learning course products.